Temporal change of genetic diversity and population structure of Plasmodium vivax in three contrasting settlements in the Peruvian Amazon - Manrique, Paulo (2019)
Background: Plasmodium vivax remains a challenge in Peru. The high heterogeneity of its transmission has limited the intervention measures based on global and generalized epidemiological information at medium and long term. Population genetic tools may provide information on the spatial heterogeneity of transmission by linking parasite genetic patterns with epidemiological information. Methods: The genetic diversity and population structures from three settlements located in the Peruvian Amazon, Cahuide (CAH), Lupuna (LUP) and Santa Emilia (STE) were measured on samples collected from September 2012 to March 2015. Results: A total of 777 P. vivax mono- infections were genotyped. LUP showed the lowest proportion of polyclonal infections (0.197) and genetic diversity (Hexp 0.544 ± 0.0012). Moreover, in this study area results showed a significant increment of polyclonal infections and Hexp (p < 0.005), and the introduction and persistence of a new parasite population from March 2014 onward. STE showed the highest proportion of polyclonal infections (0.401) and Hexp (0.596 ± 0.0028), the presence of 4 genetic clusters without signals of clonal expansion and infections with lower parasite densities compared to the other two areas. Even though CAH showed the introduction of at least 4 parasite populations in 2012, a clear reduction of cases (from 213 to 61), a subtle reduction of polyclonal infections (from 0.286 to 0.18), and an unpredicted behavior of Hexp were seen since June 2014. Conclusion: These results suggest that LUP and mainly STE are two areas that maintain basal levels of transmission, and that there are factors that allow the reintroduction of P. vivax. In contrast, malaria cases in CAH are circumstantial, thus, receptivity to malaria transmission and vulnerability to the importation of new parasite population vary drastically among the different study areas analyzed, this information must be considered in the design of current control strategies